Surgical simulators in cataract surgery training. Issue 2 (24th October 2013) - Sikder, Shameema; Tuwairqi, Khaled; Al-Kahtani, Eman; Myers, William G; Banerjee, Pat
Abstract : Background: Virtual simulators have been widely implemented in medical and surgical training, including ophthalmology. The increasing number of published articles in this field mandates a review of the available results to assess current technology and explore future opportunities. Method: A PubMed search was conducted and a total of 10 articles were reviewed. Results: Virtual simulators have shown construct validity in many modules, successfully differentiating user experience levels during simulated phacoemulsification surgery. Simulators have also shown improvements in wet-lab performance. The implementation of simulators in the residency training has been associated with a decrease in cataract surgery complication rates. Conclusions: Virtual reality simulators are an effective tool in measuring performance and differentiating trainee skill level. Additionally, they may be useful in improving surgical skill and patient outcomes in cataract surgery. Future opportunities rely on taking advantage of technical improvements in simulators for education and research.